EFEK MANAGEMENT COMMITMENT TERHADAP SERVICE ON EMPLOYEE SERVICE BEHAVIORS : PERANAN MEDIASI DARI JOB SATISFACTION - Nina Agustina; Diangtyas Diangtyas (Jurnal Manajemen dan Pemasaran Jasa, 2009)
The purpose of this paper is to examine the impact of management commitment to service on employee service behaviors and to develop and test a conceptual model of the antecedents and consequences of job satisfaction in the hospitality industry.The conceptual framework consists of the following constructs: management support, reward, empowerment, training, job satisfaction, extra role customer service behavior and cooperation. Moreover, six hypotheses were developed and tested. Instrument test of validity and reliability used to test the validity of the measures, while multiple regression was used in hypotheses testing. Data were collected from 110 respondent who are working at Sekolah Dian Harapan Daan Mogot, Jakarta Barat.Strong support was found for 1 of the 6 hypotheses. Findings reveal that management support has positive effects on job satisfaction. It is shown that reward, empowerment, training are not related to job satisfaction. Moreover, it is demonstrated that the two dimensions of service behavior— extra-role customer service behaviors and cooperation also are not related to job satisfaction. Importantly, it is found that job satisfaction can be created from employee service behavior as the school is applying the management support to the employees.Keywords: management commitment; management support; employee job satisfaction; service behaviors